POSITION OF THE TEMPOROMANDIBULAR JOINT DYSFUNCTION SYNDROME AMONG FACIAL PAIN SYNDROMES - V.L. Melnyk; V.K. Shevchenko; Yu.I. Sylenko (Український стоматологічний альманах)
At the present time, the actual problem of dentistry is the study of the issues of the syndrome of pain dysfunction (SPD) of the temporomandibular joint (TMJ), which is found in 14-20% of teenagers and significantly increases with age (Siemkin V.A, Rabukhina N.A., 2000 ; Khavatova VA, 2005). The pathology of TMJ dysfunction was detected in 80% of the examined patients (Bezrukov V.M, 2002). Separately allocated dysfunction of TMJ in dysplastic-dependent form of joint pathology, thereby emphasizing that dysfunction is a characteristic manifestation of dysplasia of connective tissue in the maxillofacial area (Statovskaia Ye.Ye, 2005; Kozlov D.L., Viazmin A.Y., 2007). According to observations of A.I Mirza, I.V. Mikheieva, V.M. Novikov and according to our data, in more than 90% of people, pathological phenomena in the area of the temporomandibular joint have nothing to do with the inflammatory processes of this combination. At the same time, various dysfunctions and pain spasm of separate areas of chewing muscles occupy the main place.